Myanmar Country Partnership Framework for the Period of FY20-FY23 - World Bank Group (World Bank, Washington, DC, 2020)
This Country Partnership Framework (CPF), which covers FY20–FY23, seeks to accompany Myanmar through a challenging and complex transition at a time when the COVID-19 pandemic is creating unprecedented uncertainty and vulnerability globally. This CPF reflects the WBG’s commitment to maintain engagement in Myanmar’s historic economic transition, but with a greater focus on inclusion, including in conflict-affected areas. The CPF program is selectively, but flexibly, defined and sequenced to leverage the WBG’s comparative advantage and optimize the impact of WBG engagement on inclusive development outcomes for Myanmar.